Circular business model experimentation: Demystifying assumptions. (20th December 2020) - Konietzko, Jan; Baldassarre, Brian; Brown, Phil; Bocken, Nancy; Hultink, Erik Jan
Abstract: Circular business model experiments may help firms transition towards a circular economy. Little is known about how the participants of experimentation – entrepreneurs, intrapreneurs, innovation managers – develop and test their assumptions during the experimentation process to achieve more circular outcomes. Using a design-science approach, we investigate this process and develop principles to improve it. This is done during three workshops in different contexts: an innovation festival with 14 early-stage circular startups, a workshop with a health technology incumbent, and a workshop with six growth-oriented startups. We find that analyzing their available means – what they find important and prefer to happen (part of their identity), what they know (their skills and knowledge), and whom they know (their social network) – helps to understand how the participants develop and test their assumptions. We show how the mindset and awareness of the participants impact how much attention they pay to the circularity potential of their envisioned circular business models. Based on these insights, we propose a set of principles to prepare the innovation participants for experimentation, and to increase their ability to reflect on their circularity assumptions. Future research is needed to further grow our understanding of the types of principles that can guide meaningful experimentations towards a circular economy.